Nomenclatural changes and redescriptions in Plateros Bourgeois, 1879 (Coleoptera: Lycidae) from Neotropical region - Nascimento, Elynton Alves Do; Bocakova, Milada (Zootaxa, 2012)
Several nomenclatural acts are proposed in this paper. Plateros plaumanni n. nov. is proposed for Sculptocalleros discithorax Pic, 1949 as a replacement name. Following 3 varieties are elevated to species rank and transferred to the genus Plateros from Calleros: Plateros curtebilineatus (Pic, 1934) comb. et stat. nov. for Calleros brasiliensis var. curtebilineatus Pic, 1934, Plateros inhumeralis (Pic, 1938) comb. et stat. nov. for Calleros wagneri var. inhumeralis Pic, 1938, and Plateros grandescapularis (Pic, 1938) comb. et stat. nov. for Calleros bogotensis var. grandescapularis Pic, 1938. Simultaneously, Plateros brasiliensis (Lucas, 1857), P. wagneri (Pic, 1923), P. bogotensis Kirsch, 1865; P. duomaculatus Kazantsev, 2011, and P. cristifer Kazantsev, 2011 are redescribed.